Políticas públicas de economia solidária : uma alternativa para o desenvolvimento local - Meira, Rodrigo Nunes (2013)
Social economy has grown in a significant way in recent decades in Brazil. This growth has enabled an alternative for economic and social inclusion of a significant portion of the population. Simultaneously, the debate on the social economy has gained power and reached the sphere of the state. The institutionalization of public policies for the sector represented an innovation within the Brazilian public management, to the extent that the role played by civil society was paramount. This study analyzes the institutionalization of social economy public policies in Brazil, considering the role the state can play in promoting economic and social development.